“Troops without Banners”: History of 5th Infantry Corps of Russian Army during Reign of Nicholas I - S. V. Andriainen (Научный диалог)
The history of the 5th Infantry Corps of the Russian Imperial Army in 1831—1853 is considered in the article. The novelty of the research lies in the fact that for the first time a comprehensive analysis of the entire history of the 5th Corps, from the moment of its formation to the beginning of the Crimean War, was carried out. The author notes that the 5th corps solved the widest range of problems. The question is raised that the 5th corps carried out the tasks of the strategic reserve of the Russian Empire on the southern borders. The role of corps units in construction work in the Crimea, participation in the landing forces on the Bosporus, military operations in the Caucasus and Transylvania are analyzed. The author notes that in the early 1830s the corps had a dubious reputation. In particular, the infantry regiments of the fifth corps were accused of “Polish spirit” and cowardice in the battles of the Russian-Polish war of 1830—1831. It is emphasized that the reputation of the corps in the eyes of Emperor Nicholas I was gradually improving. The author claims that since the 1840s, the 5th Corps was already a reliable army unit in the eyes of the emperor. The author argues that the involvement of the “bad reputation” corps in solving strategic problems demonstrates the limited resources of the Russian Empire in the 1830s and 1840s.